Antibodies against SARS-CoV-2 in children and adolescents: a one-year longitudinal study - Cristiane Feitosa Salviano; Luciana de Freitas Velloso Monte; Ana Luiza Rosa Diniz; Agenor de Castro Moreira dos Santos Júnior; Ricardo Camargo; Isis Maria Quezado Magalhães; Elisa de Carvalho; Valdenize Tiziani (BMJ Paediatrics Open)
Background The humoral response to SARS-CoV-2 is not fully understood, especially in children. This study provides valuable insights into the durability of adaptive immunity in paediatric patients who were unvaccinated and naturally infected with the prototype strain of SARS-CoV-2, including those who were asymptomatic or had pre-existing chronic and rare disorders. This study aimed to analyse the antibody response to SARS-CoV-2 during infection and over a 1-year follow-up period in patients aged 0–18 years who were admitted to a tertiary paediatric hospital at the onset of the COVID-19 pandemic.Methods This is a descriptive, prospective 1-year cohort study carried out in children and adolescents hospitalised for different reasons from July to October 2020 who presented with SARS-CoV-2 infection. Clinical and serological data (total antibody pool) were collected during SARS-CoV-2 infection and throughout the subsequent year.Results During the study period, 122 patients with confirmed SARS-CoV-2 infection were included. Most patients (85%) had at least one serology assessed and reactive throughout 1-year follow-up, even those with asymptomatic infection or immunosuppressive conditions. The mean antibody titre levels reached their maximum value about 60 days after the initial SARS-CoV-2 infection. By the end of the 1-year follow-up, 72.46% of the 69 assessed individuals still had detectable serum antibodies. Patients with comorbidities and/or immunosuppression conditions had lower median titre levels over the year. Subjects with severe clinical presentation of COVID-19 had higher levels of antibody values at the 1-year time point assessment.Conclusions This study demonstrated that most subjects presented antibody response against SARS-CoV-2 over 1 year of follow-up, even if they had asymptomatic infection or comorbidities, including patients with immunosuppression. There was a difference in the magnitude and duration of antibody response, lower in patients with comorbidities and longer and higher in subjects who had severe COVID-19 clinical presentation.